The Phenomena of Local Public Transportation Service: A Case Oplet in Pontianak, Indonesia - Setiawan, Agus; Rifai, Andri Irfan; Prasetijo, Joewono (DAS Institute, 2022)
Indonesia has a large population and high mobility in daily activities. In meeting mobility needs, traditional public transport has become a hallmark of every city. However, changes in societal behavior have caused traditional public transport to be replaced by online transportation. The purpose of this study was to determine the level of user satisfaction with traditional public transport. The research was conducted in Pontianak City with traditional public transport (Oplet) passengers as respondents. Data collection for October 2022 through an online survey. The study's Importance Performance Analysis results show that there still needs to be a gap between importance and performance. The mean importance value is 4.09 with a performance of 3.87, so the gap is 0.22. While the parameters to improve Oplet services are passenger capacity and driver communication.